Old camps, New concentrations. 1939 Spanish Republican exclusions and today’s refugees - Naharro-Calderón, José María (Hispania Nova, 2019)
The modern tradition of forced planetary displacements has continued during the Twentieth First Century, while democratic systems curtail inalienable rights. Nevertheless, The Crow Manuscript by Max Aub, states that “it is well known that wars and concentration camps are long gone”. This ironic declaration, contemporary to Joaquim Amat-Piniella’s, Hannah Arendt’s or Primo Levi’s books about camps and totalitarianisms, is premonitory of the concentration system resilience as a generalized form of repression in modern times. Well before Giorgio Agamben refurbished the camp through his homo sacer, plural Spain Republicans’ experiences in the French Third Republic and Vichy concentration camps had already anticipated and displayed them as an inherent method of modern exclusion and set back in rights.